Risk factors associated with cognitive impairment in patients with COVID-19: a protocol of systematic review and meta-analysis - Yingying Jiang; Chan Chen; Tao Zhu; Mingyuan Chen; Bo Jiao; Shuanger Li (BMJ Open, 2023)
Introduction COVID-19 infections have become a global public health emergency. Although COVID-19 is primarily a respiratory disease, some of hospitalised patients exhibit cognitive impairment-related neurological damage. Using a systematic review and meta-analysis, we aim to investigate the risk factors for cognitive impairment in patients with COVID-19.Methods and analysis This meta-analysis has been registered with the International Prospective Register of Systematic Reviews. From inception to 5 August 2022, we will search PubMed, Web of Science, Embase via Ovid, the Chinese Biological Medical Database and the Cochrane Central Register of Controlled Trials (CENTRAL) for relevant studies . We will also look for additional studies in the reference lists of selected articles. To ensure data quality and accuracy, only researches published in English and Chinese will be included. Fixed or random-effects model will be used to calculate the relative risk (RR) or odds ratio (OR) and 95% CIs for pooled data about dichotomous outcomes. We will also assess heterogeneity using Cochrane’s Q and I2 tests. Cognitive impairment RR or OR is the primary outcome.Ethics and dissemination Data will be extracted from published studies, so ethical approval is not required. The outcomes of this meta-analysis will be published in a journal with peer review.PROSPERO registration number CRD42022351011.